Perícia ambiental no crime contra a flora do bioma Mata Atlântica : análise jurisprudencial do impacto da perícia nas decisões - Trevizan, Émili Mezzomo (2022)
The Atlantic Forest Biome has been suffering from degradation for a long time. Law 9.605/1998, through article 38-A, began to protect the native vegetation of the biome through penalties applied to those who destroy, damage, or use in breach of protection rules. In legal context, expertise is highlighted, acting as an instrument for obtaining evidence that helps in the protection of the environment. In this context, it is questioned whether the expert report on crimes that affect the flora of the Atlantic Forest Biome in RS is restricted to the proof of materiality and what their effects are with regard to judicial decisions. In general, this study aims to evaluate the function and effects of the expert report in crimes that affect the flora of the Atlantic Forest Biome, provided for in article 38-A of Law 9.605/1998, through the decisions of the Court of Justice of the State of Rio Grande do Sul - TJRS (spatial delimitation), between the years 2015 and 2020 (temporal delimitation). Therefore, the method used was the hypothetical deductive, with the use of a literature review technique, and empirical jurisprudential research through the analysis of judgments published on the TJRS electronic portal, on the internet, between the years 2015 and 2020. It was found that, in addition to proving the materiality of the crime, the expert report has other functions, such as describing, quantifying, characterizing the damage, and economically valuing the environmental crime in persecutio criminis. The damage or destruction of important endangered species belonging to the Atlantic Forest Biome, when indicated in the expert report, generate a penological impact on the defendant, also implying the repair of the damage caused to the environment, and its future preservation.